Vegetation Analysis of Woody Species of some forests of Chakrata Himalayas-india - Singhal, R. M.; Rawat, V. R. S.; Kumar, Pramod; Sharma, S. D.; Singh, H. B. (Indian Forester, 1986)
A detailed phytosociological analysis of woody species of Chakrata forest at twelve different sites supporting seven tree species viz., Cedrus deodara, Pinus roxburghii, Picea smithlana, Pinus wollichiona, Quercus florihunda, Q. semicarpifolia and Abies pindrow was carried out. Their total basal cover varied between 1455 and 5672 cm2 100 m-2 and total density from 0.7 to 3.7 trees 100 m-2. The distribution pattern was random for most of the species. The species diversity was greatest in Pinus wallichlana forests followed by Quercus floribunda forests. However, the values of concentration of dominance, exhibited inverse relationship with the species diversity.